Evaluasi Pembelajaran Daring di Sekolah Menengah Kejuruan pada Masa Pandemi Covid-19 - Irma Faryani; Dwiprima Elvanny Myori (Jurnal Pendidikan Teknik Elektro, 2022)
The purpose of this study was to examine how online learning became possible due to COVID 19 when an old form of learning process was shifted to online learning. The students who are used to face-to-face learning must be exposed to the realities of learning online using online media. In order to discover the progress of online learning at school, one method is to expand existing online learning. The aim of this research is to evaluate online learning in Basic Electrical and Electronics subjects at SMK Semen Padang 2020/2021. In this study, quantitative research methods were used and research instruments were questionnaires. Based on the results of the research, the teachers and students have completed online learning well with the completion of learning beyond the minimum grade limit in a class. Using questionnaires about the online learning process, we obtained good results in this category, and questionnaires about learners' interests provided high results in this category. In conclusion, the implementation of the learning process for DLE subjects at SMK Semen Padang has been carried out effectively based on the three assessments.